Development of Particle Board Biocomposite From Coffee Skin and Tofu Dregs With Polyethylene Plastic Adhesive As Furniture Interior - Hidayat, Ali Nurdin; Permana, Edwin; Wijaya, Dhian Eka; Pratama, Yoga; Zufri, Fauzi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The need for particle board interiors is still in great demand to be used as wood-sourced interiors. In line with this, currently the problem of waste is still a fairly complex problem, both organic and inorganic waste. Coffee rinds and tofu pulp are organic wastes that have not been optimally utilized. Therefore, research was conducted on the manufacture of particleboard from coffee rinds and tofu pulp with PP plastic adhesive which aims to reduce the rate of deforestation due to tree felling as raw material for interior manufacturing and to control the environment by utilizing waste in the community into functional products. This study aims to determine the best formulation of particleboard made from Polyethylene plastic, coffee bean hulls and tofu pulp. Tofu dregs need to be preserved by soaking the dregs for 48 hours in a 5% glycerol solution and 15% NaCl solution in a 50:50 ratio. Then soaked for 48 hours. soaking 15.121%. To determine a good particleboard formulation, a physical evaluation of the particleboard was carried out including particleboard density test, water absorption test, moisture content test, thickness development test and instrumentation testing using SEM to see the surface structure of the particleboard.  Based on the results of physical testing, the best formulation of particleboard biocomposites was obtained, namely the ratio of 70:30 (% w/b) (70% of tofu pulp and coffee bean skin and 30% of PET plastic) which is in accordance with SNI 03-2105-2006 standards. Biocomposite particleboard formulation 70:30 (% w/b) has a density of 0.60186 gr/cm3, water absorption of 95.395%, moisture content of 2.248% and an increase in thickness after soaking of 15.121%.